An investigation into the current state of education in Design for Additive Manufacturing - Borgianni, Yuri; Pradel, Patrick; Berni, Aurora; Obi, Martins; Bibb, Richard (Journal of engineering design, 2022)
Additive Manufacturing (AM) has become an established discipline in both research and education. However, to achieve its full potential AM requires a step-change in design thinking, which makes Design for AM (DfAM) education and training crucial. This paper reports results from the first attempt to investigate the uptake of DfAM in higher education. This research required the development and administration of an articulated online survey, in which educators worldwide who teach AM and DfAM have participated. The results show that DfAM is taught in a considerable number of courses. However, the survey revealed that DfAM is seldom recognised as a distinct course or topic and the relevance attributed and proportion of teaching dedicated to DfAM within wider AM is typically marginal. DfAM is being mostly taught in North America and Europe and is also typically taught in institutions that are research active in AM or specifically DfAM, suggesting the subject has not yet reached maturity or diffusion into mainstream design and engineering curricula. It was interesting to find that currently, the contents of courses do not differ significantly between engineering and design programmes.